Local political leadership and the governance of urban security in Belgium and the Netherlands. (May 2013) - Devroe, Elke
In this paper, the meaning of the 'governance of security' in Belgium and the Netherlands will be explored. It is argued that the role of the mayor is substantial in both countries. This is why this article focuses explicitly on the political leadership of the mayor. The first section provides a comparison between Belgium and the Netherlands, contrasting their different constitutional-legal settlements and the relationship of these two cultures of control in the two countries. The consequences for which authorities and actors are 'responsibilized' for undertaking strategies of urban security governance are discussed. In a following section, the paper examines the current and potential challenges for governing urban security across both countries. In the final section, the dilemma of politics and science as drivers of policy responses to urban security problems is considered, identifying in particular certain deficits in mayoral expertise and training. The paper concludes that, despite a common tendency in comparative politics to group the 'Low Countries' together (given their strong historical and cultural connections), a powerful contrast is highlighted between the effects of federal and unitary constitution-legal settlements on policy responses to urban security.